Hubungan literasi gizi anak sekolah dengan status gizi pada murid kelas v dan vi di SDN 7 Wel-Wel Kecamatan Simeulue Tengah Kabupaten Simeulue - Janita Puji Ramadini; Alfridsyah Alfridsyah; Agus Hendra Al Rahmad; Siti Fainurryzky Annisa (DAPU Aceh Publishing, 2025)
The health situation of school-age children is not in line with the expected conditions. The health conditions of school-age children are often strongly related to food consumption behavior and clean and healthy living behavior. The number of school-age children was 482 people and 149 people (30.9%) were malnourished. The purpose of this study was to see the relationship between school children's nutritional literacy and nutritional status in fifth and sixth grade students at Sdn 7 Wel-Wel, Central Simeulue District, Simeulue Regency. This study is descriptive analytic with a Cross Sectional approach with a population of 33 people, the sampling technique is Total Sampling with a sample size of 33 people. Results is most of the respondents had a good nutritional status category as many as 13 people (39.4%), less knowledge about food ingredients, types and functions of nutrients as many as 17 people (51.5%), sufficient knowledge about healthy snacks as many as 14 people (42.4%), less knowledge about breakfast as many as 13 people (39.4%), knowledge about balanced nutrition p value 0.020, knowledge about food ingredients, types and functions of nutrients p value 0.010, knowledge about healthy snacks p value 0.008, knowledge about breakfast p value 0.029. There is a relationship between the nutritional literacy of school children and the nutritional status of students. It is expected to always improve knowledge by exploring information about child nutrition and good nutrition.